Implementation Of Electronic-Based Early Detection Of Preschool Children's Growth Using Elencode In Lamongan - Lilis Maghfuroh; Sylvi Harmiardillah; Harnina Samantha Aisyah; Wahyu Retno Gumelar (Universitas Serang Raya, 2022)
This community service is carried out in Sugio Lamongan. Sugio village consists of five hamlets, namely Caron, Bulus, Gondangwaruk, Pandanan, and Sugio hamlets. To find out whether there are growth and development problems, it is necessary to detect early growth and development of preschool children and one way so that preschool children get early detection of growth and development is to empower the community in this case by involving PAUD teachers. PAUD teachers can carry out early detection of growth and development continuously or continuously at the end of the semester, media or tools in the form of applications are needed so that PAUD teachers can carry out early detection of electronic-based growth and development. With the increase in science and technology, the internet can be reached to villages including Sugio village. The community service method is carried out with ELENCODE socialization lectures and assistance in implementing early detection of growth and development of preschool children with ELENCODE so that there is an increase in PAUD teacher knowledge about early detection of growth and development and improvement of electronic-based early detection skills of growth and development using ELENCODE.